KINERJA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA DARUL IHSAN MUHAMMADIYAH SRAGEN - Muhammad, Jibran; Ariyanto, Darojat (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2020)
The progress of the educational process is influenced by two main factors, namely teachers and students. The balance between good teacher performance and optimal student achievement. The purpose of this study is to describe the performance of Islamic Education teachers in improving student achievement and to describe the achievement of students at SMP Darul Ihsan Muhammadiyah Sragen. This research is qualitative. Analysis of research data using the deductive method, starting from the formulation of the theory and then ending with the phenomenon of the research results. The results of this study indicate that professional teacher performance includes creativity and innovation in learning for students, namely by the enthusiasm of the students who attend learning clinics established by the relevant teachers every evening. Teachers with their performance relate lessons by always providing opportunities for students to take part in various competition events according to their talents. While the skills to carry out performance in teaching the teacher never allow an empty class. Then the form of student achievement is, in the cognitive realm, the ability to capture lessons and the results of academic competition with other students. In the affective realm, there is an example from a teacher, habits with peers, and a high spirit of empathy. In the psychomotor domain, there is an activity guide for daily skill activities in dormitories, for example, sermons, speeches, press activities, and sports skills.